Lithium ion secondary battery

By using high silicon content silicon carbon materials, fluorovinyl carbonate, aluminum and nitrogen polymer particles in lithium-ion secondary batteries, the safety performance and cycle stability problems during fast charging are solved, and high energy density and fast charging are achieved.

CN119890408AActive Publication Date: 2025-04-25ZHUHAI COSMX BATTERY CO LTD

Patent Information

Application Number
CN202411995764.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-25
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

Existing lithium-ion secondary batteries have problems of safety performance threats and poor cycle stability during fast charging, especially the degradation of battery performance caused by the collapse of the lattice structure of the positive electrode active substance and the decrease in the electrode potential of the negative electrode sheet under high voltage conditions.

Method used

A silicon carbon material with high silicon content is used as the negative electrode active material, and an appropriate amount of fluorovinyl carbonate is added to the electrolyte to form a stable SEI film to reduce side reactions and improve safety performance. At the same time, aluminum elements are added to the cathode active coating to stabilize the lattice structure of lithium cobalt oxide, and polymer particles containing nitrogen elements are used in the separator to form a CEI film to enhance cycle stability.

Benefits of technology

It realizes that under high charging cutoff voltage, the battery has high energy density, fast charging capability, excellent cycle stability and high temperature safety performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119890408A_ABST
    Figure CN119890408A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to a lithium ion secondary battery. Comprising a negative plate, a positive plate, a diaphragm and electrolyte, the charging cut-off voltage of the battery is greater than or equal to 4.48 V; the negative plate comprises a silicon carbon material with the silicon element content of 30-80%; the positive plate comprises a positive active coating, the positive active coating comprises lithium cobalt oxide, the lithium cobalt oxide comprises an aluminum element, and the mass content of the aluminum element in the positive active coating is 6000-15000ppm; the diaphragm comprises an organic coating, and the organic coating faces the positive plate; the organic coating comprises polymer particles containing a nitrogen element, the thickness of the organic coating is 0.5-4 microns, and the mass content of the nitrogen element in the organic coating is 10.5-55%; the electrolyte comprises fluoroethylene carbonate, and the mass content of the fluoroethylene carbonate in the electrolyte is 5%-30%. The battery disclosed by the invention can give consideration to high energy density, rapid charging capability, excellent cycling stability and high-temperature safety performance under high charging cut-off voltage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a lithium-ion secondary battery. Background Art

[0002] In order to improve the energy density of the battery, silicon-based materials with high silicon content (for example, the silicon content in the silicon-based material is 30%-80%) are usually used as negative electrode active materials, and the battery's charging cut-off voltage is increased to increase the capacity of the positive electrode sheet so that it can cooperate with the high-capacity negative electrode sheet, thereby achieving the purpose of improving the battery's energy density. However, the following problems will exist during fast charging: First, silicon-based materials with high silicon content have violent side reactions under fast charging conditions and generate a lot of heat, which seriously threatens the safety performance of the battery. Second, under high voltage conditions, as the battery is charged and discharged, the lattice structure of the positive electrode active material (such as lithium cobalt oxide) will collapse, resulting in poor cycle stability of the battery. Especially during fast charging, the electrode potential of the negative electrode sheet will decrease, and the potential of the positive electrode sheet will be higher, which will seriously affect the cycle stability of the battery. Summary of the invention

[0003] The purpose of the present invention is to overcome the above problems existing in the prior art and provide a lithium ion secondary battery. The lithium ion secondary battery of the present invention (hereinafter referred to as the battery) can take into account high energy density, fast charging capability, excellent cycle stability and high temperature safety performance at a high charging cut-off voltage (≥4.48V).

[0004] The present invention provides a lithium ion secondary battery, comprising a negative electrode sheet, a positive electrode sheet, a separator and an electrolyte; the charging cut-off voltage of the lithium ion secondary battery is ≥4.48V; the negative electrode sheet comprises a silicon-carbon material, the mass content of silicon in the silicon-carbon material is 30%-80%; the positive electrode sheet comprises a positive electrode active coating, the positive electrode active coating comprises lithium cobaltate, the lithium cobaltate contains aluminum, and the mass content c of the aluminum in the positive electrode active coating is 6000ppm-15000ppm; the separator comprises an organic coating, the organic coating faces the positive electrode sheet; the organic coating comprises polymer particles, the polymer particles contain nitrogen, and the thickness h of the organic coating is 0.5μm-4μm; the electrolyte comprises fluoroethylene carbonate, the mass content of fluoroethylene carbonate in the electrolyte is 5%-30%; the mass content of nitrogen in the organic coating is 10.5%-55%.

[0005] Based on the mass content of silicon in silicon-carbon materials, there are many reaction sites with the electrolyte, which leads to aggravated side reactions. Therefore, it is necessary to add an appropriate amount of fluoroethylene carbonate to the electrolyte. Fluorinated ethylene carbonate can help form a stable SEI (Solid Electrolyte Interface) film on the surface of silicon-carbon materials to reduce the surface fragmentation and recombination process of silicon particles during high-rate charge and discharge, which can not only reduce the occurrence of side reactions between silicon-carbon materials and electrolytes, but also improve the high-temperature safety performance of batteries. It can also reduce the consumption of active lithium due to the rupture and recombination of the SEI film, thereby preventing the continuous delithiation of the positive electrode active material, which is beneficial to the structural stability of the positive electrode active material. However, it is necessary to control the mass content of fluoroethylene carbonate in the electrolyte. If it is too much, the high-temperature performance of the battery will deteriorate, thereby affecting the high-temperature safety; if it is too little, it will not protect the silicon-carbon material, which is not conducive to the high-temperature safety performance and cycle stability of the battery.

[0006] As the battery charging cut-off voltage increases, the potential on the positive electrode side also increases, which poses a greater challenge to the stability of the lithium cobalt oxide lattice structure. On the one hand, aluminum can form a large Al-O bond with the element O in lithium cobalt oxide, thereby effectively inhibiting the escape of lattice oxygen; on the other hand, Al 3+ The stability in the octahedral structure of lithium cobalt oxide is stronger, which makes it more difficult to transform lithium cobalt oxide into a monoclinic system, thereby reducing the kinetics of monoclinic formation and inhibiting the phase change of lithium cobalt oxide. Therefore, by regulating the mass content of aluminum in the positive electrode active coating, the effect of stabilizing lithium cobalt oxide can be achieved. However, it does not mean that the greater the content of aluminum, the better. This is because when the content of aluminum increases, the gram capacity of lithium cobalt oxide will be reduced, thereby affecting the overall energy density of the battery. Therefore, it is necessary to regulate the mass content of aluminum in the positive electrode active coating. When a specific range is met, it can ensure that the positive electrode sheet can work stably at high voltage (for example, 4.48V and above), and ensure that the positive electrode sheet has sufficient capacity to play, and will not cause a loss of energy density due to excessive mass content of aluminum.

[0007] At the same time, the inventors of the present invention have also conducted a large number of targeted studies and found that the direct reason for the poor stability of lithium cobalt oxide at high voltage lies in the silicon-carbon material in the negative electrode sheet. This is because the silicon-carbon material has volume expansion / contraction during the battery charge and discharge cycle, which causes the SEI film on the surface of the negative electrode sheet to continuously rupture and reorganize, and this process will continuously consume the active lithium in the battery. With the continuous consumption of active lithium, lithium ions cannot return to the lattice structure of lithium cobalt oxide, resulting in less and less lithium in the lattice structure of lithium cobalt oxide, and even by regulating the content of aluminum elements, the structural collapse cannot be prevented. When the organic coating includes polymer particles containing nitrogen elements, the polymer particles can complex the transition metal ions dissolved from the positive electrode sheet, and when the mass content of nitrogen elements in the organic coating is within a specific range, a stable CEI (Cathode Electrolyte Interphase) film can be formed on the surface of the positive electrode sheet. Therefore, the inventors of the present invention have improved the diaphragm, set an organic coating in the diaphragm, and make the organic coating contain polymer particles with nitrogen elements, and at the same time, the organic coating is facing the positive electrode sheet. The polymer particles mentioned above can stabilize the crystal structure of lithium cobalt oxide, reduce the release of active oxygen, and synergize with the aluminum element in the positive electrode active coating to improve the overall cycle stability of the battery.

[0008] Furthermore, the present invention also controls the thickness of the organic coating, which enables the battery to further balance energy density and cycle stability. This is because: if the thickness of the organic coating is too thick, the volume energy density of the battery will be low; and if it is too thin, it cannot effectively stabilize the crystal structure of lithium cobalt oxide. Therefore, when the thickness of the organic coating is within a specific range, the battery can balance energy density and cycle stability.

[0009] Through the above technical scheme, the present invention has at least the following advantages compared with the prior art: the battery of the present invention can take into account high energy density, fast charging capability, excellent cycle stability and high temperature safety performance at a high charging cut-off voltage (≥4.48V).

[0010] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] Figure 1 Shown is the XRD diffraction pattern of the organic coating in one example of the present invention.

[0012] Figure 2FIG. 1 is a schematic diagram (top view) of a groove on the surface of a negative electrode sheet in an example of the present invention, wherein: Figure 2 (a) The grooves are arranged continuously; Figure 2 (b) The grooves are arranged in sections.

[0013] Figure 3 FIG. 1 is a schematic diagram of the width of a groove in an example of the present invention, wherein Figure 3 (a)- Figure 3 The two long sides of the groove in (c) are straight lines. Figure 3 The two long sides of the groove in (d) are curved lines.

[0014] Figure 4 FIG. 1 is a schematic diagram of the spacing of grooves in an example of the present invention, wherein Figure 4 (a) is the case where two adjacent long sides are straight and parallel. Figure 4 (b) is the case where two adjacent long sides are straight lines and not parallel. Figure 4 (c) is the case where two adjacent long sides are curved lines.

[0015] Figure 5 FIG. 1 is a schematic diagram showing the structure of a winding core in an example of the present invention.

[0016] Figure 6 The figure shows a schematic diagram of the structure of the positive electrode sheet in an example of the present invention, wherein Figure 6 (a) is a top view, Figure 6 (b) is a cross-sectional view along the thickness direction.

[0017] Figure 7 FIG. 1 is a schematic top view of the first surface of the positive electrode sheet in an example of the present invention. DETAILED DESCRIPTION

[0018] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0019] The present invention provides a lithium ion secondary battery, the lithium ion battery comprising a negative electrode sheet, a positive electrode sheet, a separator and an electrolyte. The charging cut-off voltage of the lithium ion secondary battery is ≥4.48V, for example, 4.48V, 4.5V or 4.53V. The term charging cut-off voltage has a conventional meaning in the art, and generally refers to the maximum voltage value that the battery can safely reach during charging.

[0020] In the present invention, the negative electrode sheet comprises a silicon-carbon material, wherein the mass content of silicon in the silicon-carbon material may be 30%-80%, for example, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75% or 80%.

[0021] In the present invention, the mass content of silicon in the silicon-carbon material can be tested by conventional methods in the art, for example, after the battery is discharged to 0% SOC, the negative electrode sheet is disassembled and taken out, and then soaked in dimethyl carbonate (DMC) solvent for 12 hours, and then rinsed with DMC solvent to remove the lithium salt attached to the negative electrode sheet, and the negative electrode sheet is cut using an argon ion milling instrument CP laser, and then observed using a scanning electron microscope (SEM) (high voltage mode Back-scattered Electrons BSE). In this mode, the contrast of the silicon-carbon material is brighter (which can be used to distinguish the graphite material and the conductive agent in the negative electrode active coating). Combined with an energy dispersive spectrometer (EDS), at least 10 silicon-carbon materials are randomly selected, and the silicon-carbon materials are scanned to obtain the mass content of silicon in each particle, and the average value is taken.

[0022] In the present invention, the positive electrode sheet includes a positive electrode active coating. The positive electrode active coating includes lithium cobaltate. The lithium cobaltate contains aluminum element, and the mass content c of the aluminum element in the positive electrode active coating can be 6000ppm-15000ppm, for example, 6000ppm, 7000ppm, 8000ppm, 9000ppm, 10000ppm, 11000ppm, 12000ppm, 13000ppm, 14000ppm or 15000ppm.

[0023] In one embodiment, c is 6500 ppm-12000 ppm.

[0024] In the present invention, the mass content c of aluminum element in the positive electrode active coating can be obtained by testing by conventional methods in the art, for example, using an inductively coupled plasma-optical emission spectrometer (ICP-OES). The specific testing method is as follows: the battery is discharged to 0% SOC, the positive electrode sheet is disassembled and taken out, and soaked in a DMC solvent for 12 hours; then the DMC solvent is used for elution to remove the lithium salt attached to the positive electrode sheet, and the positive electrode active coating is gently scraped off from the surface of the positive electrode current collector after calcination at 400° C. in a muffle furnace for 3 hours, and the mass content of aluminum element is measured by ICP-OES (in ppm, i.e., one part per million). The specific operation method is performed in accordance with GB / T 30902-2014.

[0025] In the present invention, the separator includes an organic coating, the organic coating faces the positive electrode sheet. The organic coating includes polymer particles. The polymer particles contain nitrogen. The thickness h of the organic coating can be 0.5 μm-4 μm, for example, 0.5 μm, 1 μm, 2 μm, 3 μm or 4 μm.

[0026] In one example, h is 1 μm-2 μm.

[0027] In the present invention, the thickness h of the organic coating can be tested by conventional methods in the art, for example, the battery is discharged to 0% SOC, the diaphragm is disassembled and taken out, and it is immersed in DMC solvent for 12 hours; then it is rinsed with DMC solvent to remove the lithium salt attached to the diaphragm, and the diaphragm is cut along the thickness direction using an argon ion milling instrument CP laser, and at least 20 points are randomly selected on the organic coating in combination with SEM, and the thickness of the organic coating at each point is measured to take the average value.

[0028] In the present invention, the mass content of nitrogen in the organic coating may be 10.5%-55%, for example, 10.5%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50% or 55%.

[0029] In one example, the mass content of nitrogen in the organic coating is 15%-35%.

[0030] In the present invention, the average particle size of the polymer particles may be 0.2 μm-5 μm, for example, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, 2 μm, 3 μm, 4 μm or 5 μm.

[0031] In one example, the average particle size of the polymer particles is 0.2 μm-2 μm. The average particle size of the polymer particles can be obtained by laser particle size analyzer testing or SEM testing.

[0032] In the present invention, the electrolyte includes fluoroethylene carbonate. The mass content of fluoroethylene carbonate in the electrolyte may be 5%-30%, for example, 5%, 10%, 15%, 20%, 25% or 30%.

[0033] In the present invention, the mass content of fluoroethylene carbonate in the electrolyte can be measured by conventional methods in the art, such as gas chromatography (GC).

[0034] In the present invention, the chemical formula of lithium cobalt oxide can be Li a Co b M 1 c O2, where 0.8≤a≤1.05, 0.85≤b<1, 0 <c≤0.15,M 1Including at least one of Al, Mg, Ti, Y, La, Ga, Ge, Sn, Si, Zr, Ca, Sb, In, Ni and Mn. Lithium cobalt oxide may include first particles and second particles, the average particle size of the first particles may be 0.3μm-7μm (for example, 0.3μm, 0.5μm, 1μm, 2μm, 3μm, 4μm, 5μm, 6μm or 7μm), and the average particle size of the second particles may be 7.5μm-40μm (for example, 7.5μm, 10μm, 15μm, 20μm, 25μm, 30μm, 35μm or 40μm). The use of lithium cobalt oxide with first particles and second particles having different average particle sizes can directly affect the filling effect of lithium cobalt oxide powder during compression through the difference in particle size distribution, thereby affecting the compaction density and electronic conductivity of lithium cobalt oxide, which is beneficial to improving the overall energy density and fast charging capability of the battery.

[0035] In the present invention, the average particle size of the first particles and the average particle size of the second particles can be tested and obtained by conventional methods in the field. For example, after the battery is discharged to 0% SOC, the positive electrode sheet is disassembled and taken out, and then soaked in DMC solvent for 12 hours, and then rinsed with DMC solvent to remove the lithium salt attached to the positive electrode sheet. After calcination at 400°C in a muffle furnace for 3 hours, the positive electrode active coating is gently scraped off the surface of the positive electrode current collector, and tested using a laser particle size analyzer. The particle size range of the first particle and the second particle can be obtained through the obtained curve.

[0036] In the present invention, the silicon-carbon material includes primary spherical particles. The average particle size of the primary spherical particles may be 1 μm-6 μm, for example, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm or 6 μm.

[0037] In one example, the average particle size of the primary spherical particles is 3 μm-5 μm.

[0038] The silicon-carbon material used in the related art is in block form, and the average particle size is about 6μm-12μm. The relatively large average particle size results in poor conductivity of the particles. And because the hardness of the silicon-carbon material is relatively large, its compaction density is relatively small, and it is difficult to meet the demand for high energy density, that is, the improvement in battery energy density is limited. By further using a primary spherical particle silicon-carbon material with an average particle size of 1μm-6μm, and the silicon-carbon has a high silicon content (for example, the mass content of silicon in the silicon-carbon material is 30%-80%), the energy density of the battery can be significantly improved; and its small particle size can improve the overall conductivity of the negative electrode sheet, which is beneficial to improve the charging speed of the battery.

[0039] In the present invention, the average particle size of the primary spherical particles can be obtained by testing by conventional methods in the art, for example, after discharging the battery to 0% SOC, disassembling and removing the negative electrode sheet, soaking it in DMC solvent for 12 hours, and then rinsing it with DMC solvent to remove the lithium salt attached to the negative electrode sheet, using an argon ion milling instrument CP laser to cut the negative electrode sheet, and then using SEM observation (high voltage mode (Back-scattered Electrons BSE)). In this mode, the contrast of the silicon-carbon material is brighter (which can be used to distinguish the graphite material and the conductive agent in the negative electrode active coating), measuring at a magnification of 5K, randomly selecting at least 20 primary spherical particles, measuring the particle size of each primary spherical particle, and taking the average value. If the number of primary spherical particles is less than 20 at a magnification of 5K, then take a mirror image again until 20 primary spherical particles are measured.

[0040] In the present invention, the mass content c of aluminum element in the positive electrode active coating and the thickness h (in μm) of the organic coating satisfy: 0.003≤c×h≤0.06, for example, 0.003, 0.004, 0.005, 0.006, 0.007, 0.008, 0.009, 0.01, 0.02, 0.03, 0.04, 0.05 or 0.06.

[0041] In one example, 0.0065≤c×h≤0.024.

[0042] As mentioned above, the structural stability of lithium cobalt oxide increases with the increase of the thickness of the organic coating; and increases with the increase of the mass content of aluminum in the positive electrode active coating. Therefore, increasing the thickness of the organic coating and the mass content of aluminum in the positive electrode active coating can make the positive electrode sheet more stable to a certain extent, thereby improving the overall cycle stability of the battery. However, the thickening of the organic coating will reduce the volume proportion of the active material in the battery, resulting in a decrease in the volume energy density of the battery; and the increase in the mass content of aluminum in the positive electrode active coating will reduce the capacity of lithium cobalt oxide, resulting in a decrease in the mass energy density of the battery. Therefore, in order to further improve the energy density of the battery while ensuring the cycle stability of the battery, the relationship between the thickness h of the organic coating and the mass content c of the aluminum in the positive electrode active coating is regulated. When c×h is large (for example, greater than 0.06), the energy density of the battery is lost more, but the improvement of the battery cycle stability is not obvious; and when c×h is small (for example, less than 0.003), the cycle stability of the battery will deteriorate. When c×h is within a specific range, the battery can further take into account energy density and cycle stability.

[0043] In the present invention, the polymer particles include at least one of a cyano group, an isocyano group, an isocyanate group, and a triazine group.

[0044] The cyano group, isocyano group, isocyanate group and triazine group can complex the transition metal ions dissolved from the positive electrode and form a stable CEI film on the surface of the positive electrode. In this way, the organic cyanide containing the above groups can diffuse to the surface of the positive electrode, thereby stabilizing the crystal structure of lithium cobalt oxide, reducing the release of active oxygen, and synergizing with the aluminum element in the positive electrode active coating to improve the overall cycle stability of the battery.

[0045] In the present invention, the polymer particles further include carbon. The ratio of the mass content of carbon to the mass content of nitrogen in the organic coating may be 0.7-7.6, for example, 0.7, 0.8, 0.9, 1, 2, 3, 4, 5, 6, 7 or 7.6.

[0046] In one example, the ratio of the mass content of carbon element to the mass content of nitrogen element in the organic coating is 1.5-4.

[0047] By adjusting the ratio of the mass content of carbon to the mass content of nitrogen in the organic coating, the effect of the organic coating on the structural stabilization of lithium cobalt oxide can be further controlled. When the above ratio is within a specific range, the organic coating can further stabilize the structure of lithium cobalt oxide, thereby improving the cycle stability of the battery.

[0048] In the present invention, the mass content of carbon and the mass content of nitrogen in the organic coating can be tested by conventional methods in the art, for example, the battery is discharged to 0% SOC, the battery is disassembled, the diaphragm that exceeds the negative electrode area (i.e., the overhang area diaphragm) is cut off, and soaked in DMC solvent for 12 hours; then rinsed with DMC solvent to remove the lithium salt attached to the diaphragm; use tape to gently stick off the first adhesive layer on the outer surface of the organic coating (if the first adhesive layer is not provided on the outer surface of the organic coating, this step is omitted), the organic coating is observed using SEM, and then combined with EDS, the particles in the organic coating are scanned at a magnification of 30K, at least 20 locations are selected, and the mass contents of carbon and nitrogen are tested respectively, and the average value is taken.

[0049] In the present invention, the XRD diffraction pattern of the organic coating has a characteristic peak at 2θ of 19.5°-23.5°. Figure 1 The XRD diffraction pattern of the organic coating in one example of the present invention is shown. It can be seen from the figure that there is a characteristic peak at 2θ of 21.54°, and the intensity of the characteristic peak is in the range of 6000-12000 (unit is au), specifically 11027 a.u.

[0050] When the XRD diffraction pattern of the organic coating has a characteristic peak within a specific angle range, and the intensity of the characteristic peak is within a specific range, it indicates that the organic coating has polymer particles containing at least one of cyano, isocyano, isocyanate and triazine groups, and the content of the above groups can effectively improve the structural stability of lithium cobalt oxide and will not have a significant adverse effect on the energy density of the battery.

[0051] In the present invention, the mass content of carbon element in the organic coating may be 40%-80%, for example, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75% or 80%.

[0052] In one example, the mass content of carbon in the organic coating is 50%-70%.

[0053] In the present invention, the separator further comprises at least one of a substrate layer, a first adhesive layer and a second adhesive layer.

[0054] In one example, the organic coating comprises the substrate layer, the organic coating located on one side of the substrate layer, the first adhesive layer located on the outer surface of the organic coating, and the second adhesive layer located on the other side of the substrate layer. The substrate layer, for example, comprises polyethylene. The first adhesive layer, for example, comprises polymethyl methacrylate (PMMA). The second adhesive layer, for example, comprises polyvinylidene fluoride (PVDF) and / or PMMA.

[0055] Providing a first adhesive layer on the outer surface of the organic coating is not only beneficial to the adhesion between the organic coating and the positive electrode, but can also be used to store electrolyte, so that the organic cyanide in the organic coating can be better diffused to the surface of the positive electrode, thereby stabilizing the stability of the lithium cobalt oxide lattice.

[0056] In the present invention, the thickness of the substrate layer may be 3 μm-6 μm, for example, 3 μm, 4 μm, 5 μm or 6 μm. The thickness of the first adhesive layer may be 0.2 μm-3 μm, for example, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm or 3 μm. The thickness of the second adhesive layer may be 0.2 μm-3 μm, for example, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm or 3 μm.

[0057] In one example, the thickness of the substrate layer is 4 μm-5 μm, the thickness of the first adhesive layer is 0.2 μm-1 μm, and the thickness of the second adhesive layer is 1.5 μm-3 μm.

[0058] In one example, the thickness of the first adhesive layer is 0.3 μm-0.8 μm, and the thickness of the second adhesive layer is 2 μm-2.5 μm.

[0059] By adjusting the thickness of the first adhesive layer, the battery can further balance energy density and cycle stability. This is because: if the thickness of the first adhesive layer is too thick, the volume energy density of the battery will be low, and the diffusion of organic cyanide in the organic coating to the surface of the positive electrode will be hindered. If the thickness of the first adhesive layer is too thin, it will affect the adhesion between the diaphragm and the positive electrode, and may cause the misalignment of the positive electrode and the diaphragm, thereby affecting the cycle stability of the battery. Therefore, a first adhesive layer of appropriate thickness can further improve the battery's ability to balance energy density and cycle stability.

[0060] In the present invention, the thickness of the substrate layer, the thickness of the first adhesive layer and the thickness of the second adhesive layer can be tested by conventional methods in the art, such as referring to the test method for the thickness h of the organic coating, which will not be repeated here.

[0061] In the present invention, the polymer particles include, for example, at least one of polyacrylonitrile, nitrile rubber, 1,3,5-triazine-2,4,6-triamine, melamine cyanurate and melamine thiocyanate.

[0062] In the present invention, the bonding force between the negative electrode sheet and the separator is greater than the bonding force between the positive electrode sheet and the separator.

[0063] During high-rate charging, lithium ions are released from the positive electrode and embedded in the negative electrode. The rate of release is much greater than the rate of embedding. Therefore, increasing the rate of lithium embedding in the negative electrode is the key to increasing the charging speed. By increasing the bonding force between the negative electrode and the separator, the interfacial gap between the separator and the negative electrode can be reduced, the ion transfer rate can be increased, and thus the charging speed of the battery can be increased.

[0064] In the present invention, the bonding force between the negative electrode sheet and the separator may be 10N / m-40N / m, for example, 10N / m, 15N / m, 20N / m, 25N / m, 30N / m, 35N / m or 40N / m. The bonding force between the positive electrode sheet and the separator is ≤10N / m, for example, 10N / m, 9N / m, 8N / m, 7N / m, 6N / m, 5N / m, 4N / m, 3N / m, 2N / m or 1N / m.

[0065] In the present invention, the bonding force between the negative electrode sheet and the diaphragm and the bonding force between the positive electrode sheet and the diaphragm can be tested by conventional methods in the art, for example, discharging the battery to 0% SOC, disassembling the battery, taking the areas where the diaphragm and the positive / negative electrode sheet are completely bonded, and using a tool to cut a spline with a size of 15 mm along the width direction (the width direction of the diaphragm) (that is, the length of the spline is the width of the diaphragm, and the width of the spline is 15 mm); using a tensile machine, fixing the diaphragm at one end and the electrode sheet (positive electrode sheet or negative electrode sheet) at the other end, peeling off the diaphragm and the electrode sheet until the two are completely peeled off, and the average peeling force of the entire peeling process is the bonding force between the diaphragm and the positive / negative electrode sheet.

[0066] In the present invention, the negative electrode sheet includes a negative electrode current collector and a negative electrode active coating located on at least one side of the negative electrode current collector. The outer surface of the negative electrode active coating may have a first recess. The first recess is provided on the surface of the negative electrode active coating, and the first recess can shorten the contact distance between the electrolyte and the negative electrode active material, reduce the polarization impedance in the thickness direction of the negative electrode sheet, and improve the dynamic performance of the negative electrode sheet, thereby improving the charging speed of the battery.

[0067] In the present invention, the first concave portion may include a concave hole or a groove. The first concave portion may be obtained by laser drilling or wire punching technology. When the first concave portion is a groove, the groove may be arranged continuously or in sections. Figure 2 FIG. 1 is a schematic diagram (top view) of a groove on the surface of a negative electrode sheet in an example of the present invention, wherein: Figure 2 (a) The grooves are arranged continuously; Figure 2 (b) The grooves are arranged in sections. As can be seen from the figure, the surface of the negative electrode sheet (i.e., the surface of the negative electrode active coating) has several grooves. Figure 2 In (a), the grooves are arranged continuously in the width direction of the negative electrode sheet. Figure 2 In (b), the grooves are arranged in sections in the width direction of the negative electrode sheet. It can be understood that Figure 2 Only the case where the groove is arranged along the width direction of the negative electrode sheet is given, and the groove can also be arranged along the length direction of the negative electrode sheet.

[0068] In the present invention, the depth of the first concave portion may be 5 μm-40 μm, for example, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm or 40 μm. The depth of the first concave portion has the conventional meaning in the art, and refers to the vertical distance from the lowest point in the first concave portion to the surface of the negative electrode sheet. The depth of the first concave portion can be obtained by testing by conventional methods in the art, for example, using a 3D profiler to test the depths of all first concave portions or at least 20 first concave portions on the surface of the negative electrode active coating, and taking an average value.

[0069] In one example, the depth of the first concave portion is 15 μm-30 μm.

[0070] In the present invention, the width of the first concave portion may be 40 μm-200 μm, for example, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 150 μm or 200 μm.

[0071] In one example, the width of the first concave portion is 60 μm-100 μm.

[0072] When the first recess is a recessed hole, the width of the first recessed portion refers to the aperture of the recessed hole. The aperture of the recessed hole has the conventional meaning in this field. When the shape of the orthographic projection of the recessed hole on the surface of the negative electrode sheet is a "regular circle", the aperture of the recessed hole is the diameter of the regular circle; when the shape of the orthographic projection of the recessed hole on the surface of the negative electrode sheet is a non-"regular circle" (such as an ellipse or an irregular curved polygon), the aperture of the recessed hole is the diameter of an equivalent circle with an area equal to that of the non-"regular circle". The aperture of the recessed hole can be obtained by conventional means in this field, such as by using a 3D profilometer, selecting all or at least 10 recessed holes, measuring the aperture, and taking the average value.

[0073] When the first concave portion is a groove, the width of the first concave portion refers to the width of the groove. The width of the groove has a conventional meaning in the art. The positive projection of the groove on the surface of the negative electrode sheet includes two long sides, and the width of the groove refers to the average distance from one long side to another long side in the length direction or width direction of the negative electrode sheet. Figure 3 FIG. 1 is a schematic diagram of the width of a groove in an example of the present invention, wherein Figure 3 (a)- Figure 3 The two long sides of the groove in (c) are straight lines. Figure 3 The two long sides of the groove in (d) are curved. Figure 3 (a) and Figure 3 In (b), the two long sides are arranged in parallel, so that in the width direction of the negative electrode sheet, the vertical distance from any point on one long side to the other long side is equal. In this case, the width of the groove is the vertical distance L1 from any point on one long side to the other long side in the length direction or width direction of the negative electrode sheet. Figure 3In (c), the two long sides of the groove are straight lines, but they are not set in parallel. Therefore, in the width direction, the size from any point on one long side to the other long side is not equal. In this case, the width of the groove can be averaged, that is, on one long side, based on the length of the side, 50 points are selected at equal distances (that is, the distance between each point is equal, so that the selection of points can make the calculation result more accurate), and the width L1 corresponding to each point is measured, and the average value is taken to obtain the width of the groove. Figure 3 In (d), the two long sides are curved. Therefore, in the width direction, the distance from any point on one long side to the other long side is not equal. In this case, the width of the groove can also be averaged, that is, 50 points are randomly selected on one long side (due to Figure 3 In (d), the two long sides are curved and do not exist. Figure 3 (c) The relationship between the two long sides, therefore, 50 points can be randomly selected for measurement), and the width L1 corresponding to each point is measured, and the average value is taken to obtain the width of the groove. The width of the groove can be obtained by conventional means in the art, such as by using a 3D profiler to test the width of all grooves or at least 5 grooves on the surface of the negative electrode active coating and take the average value.

[0074] In the present invention, the spacing of the first recesses may be 0.5 mm-5 mm, for example, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1 mm, 1.5 mm, 2 mm, 2.5 mm, 3 mm, 3.5 mm, 4 mm, 4.5 mm or 5 mm.

[0075] In one example, the interval between the first recesses is 0.8 mm-1.5 mm.

[0076] When the first concave portion is a concave hole, the spacing of the first concave portion refers to the spacing of the concave holes. The spacing of the concave holes has a conventional meaning in the art. It refers to the shortest distance between the edges of two adjacent concave holes on the surface of the negative electrode sheet. The spacing of the concave holes can be obtained by conventional means in the art, such as by selecting all or at least 10 groups of adjacent concave holes through a 3D profilometer, measuring the spacing, and taking the average value.

[0077] When the first concave portion is a groove, the spacing of the first concave portion refers to the spacing of the grooves. It is understood that when there is only one groove on the surface of the negative electrode sheet, there is no spacing of the grooves. The spacing of the grooves has the conventional meaning in the art, which refers to the average distance between the two adjacent long sides of two adjacent grooves in the length direction or width direction of the negative electrode sheet. Figure 4 FIG. 1 is a schematic diagram of the spacing of grooves in an example of the present invention, wherein Figure 4 (a) is the case where two adjacent long sides are straight and parallel. Figure 4(b) is the case where two adjacent long sides are straight lines and not parallel. Figure 4 (c) is the case where two adjacent long sides are curved. Figure 4 In (a), the two adjacent long sides are straight and parallel, so in the width direction, the distance from any point on one long side to the other long side is equal. In this case, the spacing of the grooves is the distance L2 from any point on one long side to the other long side in the width direction. Figure 4 In (b), the two adjacent long sides are straight lines, but they are not set in parallel. Therefore, in the width direction, the distance from any point on one long side to the other long side is not equal. In this case, the spacing of the grooves can be averaged, that is, on a long side, based on the length of the side, 50 points are selected at equal distances (that is, the distance between each point is equal, so that the selection of points can make the calculation result more accurate), and the width L2 corresponding to each point is measured, and the average value is taken to obtain the spacing. Figure 4 In (c), the two adjacent long sides are curved. Therefore, in the width direction, the distance from any point on one long side to the other long side is not equal. In this case, the spacing of the grooves can also be averaged, that is, 50 points are randomly selected on one long side (due to Figure 4 (c) The two long sides are curved, so there is no Figure 4 (b) The relationship between the two long sides, therefore, 50 points can be randomly selected for measurement), and the width L2 corresponding to each point is measured, and the average value is taken to obtain the spacing. The spacing of the grooves can be obtained by conventional means in the art, such as by using a 3D profilometer to test the spacing of all grooves or at least 5 grooves on the surface of the negative electrode active coating and take the average value.

[0078] In the present invention, the positive electrode sheet includes a positive electrode current collector and the positive electrode active coating located on at least one side of the positive electrode current collector. The length of the positive electrode active coating located on the first surface of the positive electrode current collector is greater than the length of the positive electrode active coating located on the second surface of the positive electrode current collector. It can be understood that when the positive electrode sheet is coated, there are single-sided coating areas and double-sided coating areas. The single-sided coating area is the positive electrode current collector located in the area, and only one side of the surface has the positive electrode active coating; while the double-sided coating area is the positive electrode current collector located in the area, and both sides of the surface have the positive electrode active coating. This leads to the situation that the length of the positive electrode active coating on both sides of the positive electrode sheet is not equal. In the present invention, the side with a relatively longer length of the positive electrode active coating on the surface of the positive electrode current collector is defined as the first surface, and the side with a relatively shorter length of the positive electrode active coating is defined as the second surface. The area where the projections of the positive electrode active coating located on the first surface and the positive electrode active coating located on the second surface overlap in the thickness direction of the positive electrode sheet is the double-sided coating area, and the area where the above projections do not overlap is the single-sided coating area. Due to the special structure of the wound battery, usually the first surface faces the winding center of the winding core, and the second surface faces away from the winding center of the winding core.

[0079] In the present invention, the surface of the positive electrode active coating located on the first surface has a second concave portion, and the surface of the positive electrode active coating located on the second surface has a convex portion. The surface of the positive electrode sheet is embossed to obtain a structure with a concave portion on one side and a convex portion on the other side. The storage position of the electrolyte inside the battery is distributed in the gap between the battery core and the shell (such as aluminum plastic film) and the interlayer gap between the positive and negative electrode sheets and the diaphragm. The storage of the electrolyte in the interlayer mainly relies on the pores and capillary effect of the electrode sheets (positive and negative electrode sheets) to slowly infiltrate. Compared with the infiltration of the gap between the battery core and the shell, the required time is longer and the difficulty is greater. Therefore, the liquid storage capacity of the interlayer gap between the positive and negative electrode sheets and the diaphragm is relatively small. The second concave portion and the convex portion are set on the surface of the positive electrode sheet, which can provide more liquid storage places, reduce the ion transmission distance, thereby reducing the polarization of the positive and negative electrode sheets, which is conducive to improving the charging speed of the battery.

[0080] The inventors of the present invention have conducted a stress analysis on the positive electrode active coating in the winding core facing the winding center and away from the winding center, and found that when a concave portion is set on the first surface facing the winding center and a convex portion is set on the second surface away from the winding center, it is not only beneficial to the structural stability of the positive electrode sheet itself; it can also provide a better buffer space for the volume expansion of the negative electrode sheet, thereby improving the cycle life of the battery.

[0081] like Figure 5The following is a schematic structural view of a core in an example of the present invention. As can be seen from the figure, the surface of the positive electrode active coating on the first surface has a second recess, and the surface of the positive electrode active coating on the second surface has a protrusion. The first surface faces the winding center of the core, and the second surface faces away from the winding center of the core.

[0082] In the present invention, the shapes of the positive projections of the second recess and the protrusion on the surface of the positive electrode sheet are not limited, and may be circular, elliptical, linear (including straight or wavy lines), polygonal and other shapes.

[0083] In the present invention, the positive electrode sheet includes a positive electrode tab welding area, a paste coating area, and a blank foil area. The paste coating area includes a double-sided coating area and a single-sided coating area. As Figure 6 The following is a schematic structural view of a positive electrode sheet in an example of the present invention, where Figure 6 (a) is a top view, Figure 6 (b) is a cross-sectional view along the thickness direction. As can be seen from the figure, the positive electrode sheet includes a positive electrode tab welding area 3, a paste coating area 4, and a blank foil area 5, where the paste coating area 4 includes a double-sided coating area 10 and a single-sided coating area 20.

[0084] In one example, the second recess and the protrusion are located in the paste coating area.

[0085] In one example, the second recess and the protrusion are located in the double-sided coating area.

[0086] In one example, the second recess and the protrusion are located in the paste coating area and in the double-sided coating area.

[0087] In the present invention, the distance from the second recess to the edge of the positive electrode tab welding area is w1, 0 mm < w1 ≤ 10 mm, for example, 0.1 mm, 0.5 mm, 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm or 10 mm.

[0088] In the present invention, the distance from the second recess to the edge of the first side of the paste coating area is w2, 2 mm ≤ w2 ≤ 40 mm, for example, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, 10 mm, 11 mm, 12 mm, 13 mm, 14 mm, 15 mm, 16 mm, 17 mm, 18 mm, 19 mm, 20 mm, 25 mm, 30 mm, 35 mm or 40 mm. The first side is the side where the positive electrode tab welding area is provided.

[0089] In the present invention, the distance from the second recess to the edge of the second side of the pasting area is w3, where 2 mm ≤ w3 ≤ 25 mm, for example, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, 10 mm, 11 mm, 12 mm, 13 mm, 14 mm, 15 mm, 16 mm, 17 mm, 18 mm, 19 mm, 20 mm or 25 mm. The second side is the side opposite to the side where the positive tab welding area is provided.

[0090] In the present invention, the distance from the second recess to the edge of the third side of the pasting area is w4, where 0 mm < w4 ≤ 20 mm, for example, 0.1 mm, 0.5 mm, 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, 10 mm, 11 mm, 12 mm, 13 mm, 14 mm, 15 mm, 16 mm, 17 mm, 18 mm, 19 mm or 20 mm. The third side is the side of the pasting area close to the first winding end.

[0091] In the present invention, the distance from the second recess to the boundary line between the double-sided coating area and the single-sided coating area is w5, where 0 mm < w5 ≤ 20 mm, for example, 0.1 mm, 0.5 mm, 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, 10 mm, 11 mm, 12 mm, 13 mm, 14 mm, 15 mm, 16 mm, 17 mm, 18 mm, 19 mm or 20 mm.

[0092] By controlling w1, w2, w3, w4 and w5, it is possible to ensure that the positive electrode sheet does not drop powder, which is beneficial to improving the cycle life of the battery.

[0093] As Figure 7 shown in the top view schematic diagram of the first surface of the positive electrode sheet in an example of the present invention, it can be seen from the figure that the first surface has a plurality of second recesses 6. The distance from the second recess 6 to the edge of the positive tab welding area 3 is w1, the distance from the second recess 6 to the edge of the first side of the pasting area 4 is w2, the distance from the second recess 6 to the edge of the second side of the pasting area 4 is w3, the distance from the second recess 6 to the edge of the third side of the pasting area 4 is w4, and the distance from the second recess 6 to the boundary line between the double-sided coating area 10 and the single-sided coating area 20 is w5.

[0094] In the present invention, the depth of the second recess can be 3 μm - 40 μm, for example, 3 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm or 40 μm. The height of the convex portion can be 3 μm - 40 μm, for example, 3 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm or 40 μm.

[0095] In one example, the depth of the second concave portion is 10 μm-30 μm, and the height of the convex portion is 10 μm-30 μm.

[0096] In the present invention, the depth of the second concave portion and the height of the convex portion have the conventional meanings in the art, and the depth of the second concave portion refers to the vertical distance from the lowest point in the second concave portion to the surface of the positive electrode sheet. The height of the convex portion refers to the vertical distance from the highest point on the convex portion to the surface of the positive electrode sheet. The depth of the second concave portion and the height of the convex portion can be obtained by testing by conventional methods in the art, for example, by using a 3D profilometer, at least 10 second concave portions and 10 convex portions are selected on the positive electrode sheet, the depth of each second concave portion and the height of the convex portion are measured, and the average values ​​are taken respectively.

[0097] In the present invention, the width of the second concave portion may be 0.2 mm to 8 mm, for example, 0.2 mm, 0.5 mm, 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm or 8 mm. The width of the convex portion may be 0.2 mm to 8 mm, for example, 0.2 mm, 0.5 mm, 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm or 8 mm.

[0098] In one example, the width of the second concave portion is 1 mm to 3 mm, and the width of the convex portion is 1 mm to 3 mm.

[0099] In the present invention, when the shape of the projection of the second concave portion in the thickness direction of the positive electrode sheet is a regular circle, the width of the second concave portion is the diameter of the regular circle; when the shape of the projection of the second concave portion in the thickness direction of the positive electrode sheet is a non-"regular circle", the width of the second concave portion is the equivalent diameter of a circle with an area equal to that of the irregular circle. Similarly, when the shape of the projection of the convex portion in the thickness direction of the positive electrode sheet is a regular circle, the width of the convex portion is the diameter of the regular circle; when the shape of the projection of the convex portion in the thickness direction of the positive electrode sheet is a non-"regular circle", the width of the convex portion is the equivalent diameter of a circle with an area equal to that of the irregular circle. The width of the second concave portion and the width of the convex portion can be obtained by conventional methods in the art, for example, by using a 3D profiler, selecting at least 10 second concave portions and 10 convex portions on the surface of the positive electrode sheet, measuring the width of each second concave portion and the width of the convex portion, and taking the average values ​​respectively.

[0100] In the present invention, the spacing of the second concave portions may be 0.5 mm to 8 mm, for example, 0.5 mm, 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm or 8 mm. The spacing of the convex portions may be 0.5 mm to 8 mm, for example, 0.5 mm, 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm or 8 mm.

[0101] In one example, the spacing between the second concave portions is 1 mm to 3 mm, and the spacing between the convex portions is 1 mm to 3 mm.

[0102] In the present invention, the spacing of the second concave portions refers to the shortest distance between the edges of the orthographic projections of two adjacent second concave portions on the surface of the positive electrode sheet, and similarly, the spacing of the convex portions refers to the shortest distance between the edges of the orthographic projections of two adjacent convex portions on the surface of the positive electrode sheet. The spacing of the second concave portions and the spacing of the convex portions can be obtained by testing by conventional methods in the art, for example, by using a 3D profilometer, selecting at least 10 groups of adjacent second concave portions and 10 groups of adjacent convex portions on the surface of the positive electrode sheet, measuring the spacing of each group of second concave portions and the spacing of each group of convex portions, and taking the average values ​​respectively.

[0103] In the present invention, the silicon-carbon material further comprises secondary spherical particles formed by a plurality of the primary spherical particles. The “several” means that the number of the primary spherical particles forming the secondary spherical particles is greater than or equal to 2.

[0104] The conventionally used silicon-carbon material is in block form, and the average particle size is about 6μm-12μm. Therefore, the conductivity is poor, and it is difficult to achieve a large compaction density, and the energy density can be improved to a limited extent. In the present invention, a silicon-carbon material including primary spherical particles is used as the negative electrode active material. Primary particles with smaller particle sizes are beneficial to improving the energy density of the battery; however, due to their smaller particle size and larger specific surface area, the risk of side reactions with the electrolyte increases accordingly, and the stability is poor. In order to further reduce the occurrence of side reactions between the silicon-carbon material and the electrolyte, secondary spherical particles formed by a number of primary spherical particles are added. Secondary spherical particles with larger particle sizes have a smaller specific surface area, so they have a lower risk of side reactions with the electrolyte and better stability.

[0105] In the present invention, the average particle size of the secondary spherical particles can be 3μm-20μm, for example, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, 18μm, 19μm or 20μm.

[0106] In the present invention, the average particle size of the secondary spherical particles can be tested by conventional methods in the art, for example, after discharging the battery to 0% SOC, disassembling and removing the negative electrode sheet, soaking it in DMC solvent for 12 hours, and then rinsing it with DMC solvent to remove the lithium salt attached to the negative electrode sheet, using an argon ion milling instrument CP laser to cut the negative electrode sheet, and then using SEM observation (high voltage mode), measuring at a magnification of 5K, randomly selecting at least 20 secondary spherical particles, measuring the particle size of each secondary spherical particle, and taking the average value. If the number of secondary spherical particles is less than 20 at a magnification of 5K, then take a mirror image again until 20 secondary spherical particles are measured.

[0107] In the present invention, in the negative electrode active coating, the amount of the primary spherical particles accounts for 0.1-0.9 of the total amount of the primary spherical particles and the secondary spherical particles, for example, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8 or 0.9.

[0108] In one example, in the negative electrode active coating, the amount of the primary spherical particles accounts for 0.3-0.8 of the total amount of the primary spherical particles and the secondary spherical particles.

[0109] In the present invention, in the negative electrode active coating, the number of the primary spherical particles and the number of the secondary spherical particles can be tested and obtained by conventional methods in the art, such as using an argon ion milling instrument CP laser to cut along the thickness direction of the negative electrode sheet, and then using SEM (high voltage mode) to obtain a mirror image of the cross-section of the negative electrode sheet along the thickness direction, and at least 20 mirror images of different cross-sections are selected, and the number of primary spherical particles and the number of secondary spherical particles in each mirror image are counted respectively, and the average value is taken.

[0110] In the present invention, the negative electrode active coating includes a negative electrode active material, and the negative electrode active material includes the silicon-carbon material. The negative electrode active material may also include a graphite material. The graphite material includes, for example, artificial graphite and / or natural graphite. The graphite material includes secondary particles. The secondary particles are formed by a plurality of primary particles. The "several" means that the number of the primary particles forming the secondary particles is greater than or equal to 2.

[0111] In the present invention, the average particle size of the secondary particles may be 6 μm-20 μm, for example, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm or 20 μm.

[0112] By using a specific graphite material and adjusting the structure and particle size of the graphite material, the graphite material includes secondary particles formed by primary particles, and the average particle size of the secondary particles is 6μm-20μm, which can further improve the energy density of the battery. Compared with the graphite material of the primary particles, the secondary particles of the graphite material with a specific particle size can improve the energy density of the battery. Therefore, the graphite material has a high degree of matching with the specific silicon-carbon material, which is conducive to the improvement of the energy density of the battery.

[0113] In the present invention, the average particle size of the secondary particles can be obtained by testing by conventional methods in the art, for example, after the battery is discharged to 0% SOC, the negative electrode sheet is disassembled and taken out, and after being soaked in DMC solvent for 12 hours, it is rinsed with DMC to remove the lithium salt attached to the negative electrode sheet, and then the negative electrode active coating is rinsed off from the negative electrode current collector with deionized water, and the filtrate is removed by centrifugation after ultrasonication, and dried, and the obtained sample is dispersed in deionized water containing nonylphenol polyoxyethylene ether (wherein the mass content of nonylphenol polyoxyethylene ether is 0.02%-0.03%) to form a mixture, ultrasonicated for 2 minutes, and then tested using a Malvern particle size tester, and the median particle size Dv50 data obtained is the average particle size of the secondary particles. Due to the specific composition and particle size of the graphite material and the silicon-carbon material in the present invention, the silicon-carbon material has little effect on the average particle size of the secondary particles of the graphite material, so the data obtained by the above test method is the average particle size of the secondary particles.

[0114] It should be noted that the numerical expressions such as "first" and "second" in the present invention are only used to distinguish different substances or usages, and do not represent the difference in order.

[0115] The present invention will be described in detail below by way of examples. The examples described in the present invention are only a part of the examples of the present invention, rather than all of the examples. Based on the examples in the present invention, all other examples obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.

[0116] In the following examples, unless otherwise specified, all materials used were commercially available analytical grade.

[0117] The following examples are used to illustrate the lithium ion secondary battery of the present invention.

[0118] Example 1

[0119] Prepare the battery as follows:

[0120] (1) Preparation of positive electrode sheet

[0121] Lithium cobalt oxide (M 1Including Al), positive electrode conductive agent (conductive carbon black) and positive electrode binder (polyvinylidene fluoride) are mixed in a mass ratio of 97:1:2, N-methylpyrrolidone (NMP) is added, stirred evenly, and prepared into a positive electrode slurry; the above positive electrode slurry is coated on the first surface and the second surface of the aluminum foil (the coating length of the positive electrode slurry on the first surface of the aluminum foil is greater than the coating length on the second surface), baked, and rolled to obtain a positive electrode sheet with a thickness of 100 μm; a positive electrode tab welding area of ​​a fixed size is set on the paste coating area of ​​the positive electrode sheet (the size of the positive electrode tab welding area in the width direction of the positive electrode sheet is 20 mm), and the nickel tab is laser welded in the above positive electrode tab welding area; and then after passing through a roller, embossing is performed from the first surface to the second surface in the double-sided coating area (and avoiding the positive electrode tab welding area) to obtain a second concave portion (first surface) and a convex portion (second surface); the shape of the orthographic projection of the second concave portion and the convex portion on the surface of the positive electrode sheet is circular;

[0122] Among them, the mass content c of aluminum element in the positive electrode active coating is 8166ppm, the width of the second recess is 2mm, the depth is 20μm, and the spacing is 2mm; w1 is 7mm, w2 is 27mm, w3 is 15mm, w4 is 7mm, and w5 is 7mm.

[0123] (2) Preparation of negative electrode sheet

[0124] Artificial graphite (secondary particles), silicon-carbon material (the number of primary spherical particles accounts for 0.55 of the total number of primary spherical particles and secondary spherical particles, the average particle size of the primary spherical particles is 4.2 μm, and the mass content of element Si in the silicon-carbon material is 40%), negative electrode conductive agent (carbon nanotubes), negative electrode dispersant (lithium carboxymethyl cellulose) and negative electrode binder (polyacrylic acid) are mixed in a mass ratio of 77:20:0.4:0.1:2.5, and deionized water is added to prepare a negative electrode slurry; the above-mentioned negative electrode slurry is coated on the surface of both sides of the copper foil, and after baking and rolling, a negative electrode sheet with a thickness of 110 μm is obtained; a first concave portion (groove) is made on the surface of the negative electrode sheet using a laser;

[0125] The width of the groove is 80.3 μm, the depth is 23.2 μm, and the spacing is 1.2 mm.

[0126] (3) Preparation of electrolyte

[0127] In a glove box (H2O<0.01ppm, O2<0.01ppm, Ar atmosphere), ethylene carbonate, propylene carbonate and diethyl carbonate are mixed in a weight ratio of 1:3:6 to obtain an organic solvent; fluoroethylene carbonate (FEC) and lithium hexafluorophosphate (LiPF6) are dissolved in the above-mentioned organic solvent to obtain an electrolyte; wherein the mass content of FEC in the electrolyte is 15%, and the mass content of LiPF6 in the electrolyte is 12.5%.

[0128] (4) Preparation of diaphragm

[0129] Polyacrylonitrile is ground, and then mixed evenly with styrene-butadiene rubber and lithium polyacrylate in a mass ratio of 95:4:1 (polyacrylonitrile: styrene-butadiene rubber: lithium polyacrylate), and NMP is added to obtain an organic coating slurry; the above-mentioned organic coating slurry is applied to one side of a polyethylene film (thickness of 4.5 μm), and dried (to form an organic coating with a thickness of 1.6 μm and an average particle size of polymer particles of 0.8 μm); a second adhesive layer of PMMA is applied to the other side of the polyethylene film (to form a second adhesive layer with a thickness of 2.3 μm), and a first adhesive layer (including PVDF+PMMA, wherein the mass ratio of PVDF to PMMA is 7:3, to form a first adhesive layer with a thickness of 0.5 μm) is applied to the outer surface of the organic coating to obtain a diaphragm, wherein the mass content of nitrogen in the organic coating is 23%, the mass content of carbon in the organic coating is 62%, and the ratio of the mass content of carbon to the mass content of nitrogen in the organic coating is 2.7.

[0130] (5) Preparation of batteries

[0131] The positive electrode sheet prepared in step (1), the separator prepared in step (4) and the negative electrode sheet prepared in step (2) are wound to obtain a winding core (wherein the organic coating faces the positive electrode sheet); a battery is obtained by packaging, baking, liquid injection, formation, secondary sealing, sorting and OCV;

[0132] Among them, c×h is 0.0131.

[0133] Example 2

[0134] Prepare the battery as follows:

[0135] (1) Preparation of positive electrode sheet

[0136] Lithium cobalt oxide (M 1Including Al), positive electrode conductive agent (conductive carbon black) and positive electrode binder (polyvinylidene fluoride) are mixed in a mass ratio of 97:1:2, N-methylpyrrolidone (NMP) is added, stirred evenly, and prepared into positive electrode slurry; the above positive electrode slurry is coated on the first surface and the second surface of the aluminum foil (the coating length of the positive electrode slurry on the first surface of the aluminum foil is greater than the coating length on the second surface), baked, and rolled to obtain a positive electrode sheet with a thickness of 100 μm; a positive electrode tab welding area of ​​a fixed size is set on the paste coating area of ​​the positive electrode sheet (the size of the positive electrode tab welding area in the width direction of the positive electrode sheet is 15 mm), and the nickel tab is laser welded in the above positive electrode tab welding area; and then after passing through a roller, embossing is performed from the first surface to the second surface in the double-sided coating area (and avoiding the positive electrode tab welding area) to obtain a second concave portion (first surface) and a convex portion (second surface); the shape of the orthographic projection of the second concave portion and the convex portion on the surface of the positive electrode sheet is circular;

[0137] Among them, the mass content c of aluminum element in the positive electrode active coating is 6523ppm, the width of the second recess is 1mm, the depth is 10μm, and the spacing is 1mm; w1 is 5mm, w2 is 20mm, w3 is 10mm, w4 is 5mm, and w5 is 5mm.

[0138] (2) Preparation of negative electrode sheet

[0139] Artificial graphite (secondary particles), silicon-carbon material (the number of primary spherical particles accounts for 0.31 of the total number of primary spherical particles and secondary spherical particles, the average particle size of the primary spherical particles is 3 μm, and the mass content of element Si in the silicon-carbon material is 40%), negative electrode conductive agent (carbon nanotubes), negative electrode dispersant (lithium carboxymethyl cellulose) and negative electrode binder (polyacrylic acid) are mixed in a mass ratio of 77:20:0.4:0.1:2.5, and deionized water is added to prepare a negative electrode slurry; the above-mentioned negative electrode slurry is coated on the surface of both sides of the copper foil, and after baking and rolling, a negative electrode sheet with a thickness of 110 μm is obtained; a first concave portion (groove) is made on the surface of the negative electrode sheet using a laser;

[0140] The width of the groove is 60.1 μm, the depth is 15.2 μm, and the spacing is 0.8 mm.

[0141] (3) Preparation of electrolyte

[0142] In a glove box (H2O<0.01ppm, O2<0.01ppm, Ar atmosphere), ethylene carbonate, ethylene carbonate and diethyl carbonate are mixed in a weight ratio of 1:3:6 to obtain an organic solvent; fluoroethylene carbonate (FEC) and lithium hexafluorophosphate (LiPF6) are dissolved in the above-mentioned organic solvent to obtain an electrolyte; wherein the mass content of FEC in the electrolyte is 10%, and the mass content of LiPF6 in the electrolyte is 12.5%.

[0143] (4) Preparation of diaphragm

[0144] 1,3,5-triazine-2,4,6-triamine and polyacrylonitrile are ground, then mixed with styrene-butadiene rubber and lithium polyacrylate in a mass ratio of 25:70:4:1 (1,3,5-triazine-2,4,6-triamine: polyacrylonitrile: styrene-butadiene rubber: lithium polyacrylate), and NMP is added to obtain an organic coating slurry; the organic coating slurry is applied to one side of a polyethylene film (with a thickness of 4 μm), and dried (to form an organic coating with a thickness of 1 μm and an average particle size of polymer particles of 0.6 μm); A second adhesive layer of PMMA is coated on the other side of the ethylene film (forming a second adhesive layer with a thickness of 2.5 μm), and a first adhesive layer (including PVDF+PMMA, wherein the mass ratio of PVDF to PMMA is 7:3, forming a first adhesive layer with a thickness of 0.3 μm) is coated on the outer surface of the organic coating to obtain a diaphragm, wherein the mass content of nitrogen in the organic coating is 33%, the mass content of carbon in the organic coating is 50%, and the ratio of the mass content of carbon in the organic coating to the mass content of nitrogen is 1.52.

[0145] (5) Preparation of batteries

[0146] The positive electrode sheet prepared in step (1), the separator prepared in step (4) and the negative electrode sheet prepared in step (2) are wound to obtain a winding core (wherein the organic coating faces the positive electrode sheet); a battery is obtained by packaging, baking, liquid injection, formation, secondary sealing, sorting and OCV;

[0147] Among them, c×h is 0.0065.

[0148] Example 3

[0149] Prepare the battery as follows:

[0150] (1) Preparation of positive electrode sheet

[0151] Lithium cobalt oxide (M 1Including Al, positive electrode conductive agent (conductive carbon black) and positive electrode binder (polyvinylidene fluoride) are mixed in a mass ratio of 97:1:2, N-methylpyrrolidone (NMP) is added, stirred evenly, and prepared into positive electrode slurry; the above positive electrode slurry is coated on the first surface and the second surface of the aluminum foil (the coating length of the positive electrode slurry on the first surface of the aluminum foil is greater than the coating length on the second surface), baked, and rolled to obtain a positive electrode sheet with a thickness of 100 μm; a positive electrode tab welding area of ​​a fixed size is set on the paste coating area of ​​the positive electrode sheet (the size of the positive electrode tab welding area in the width direction of the positive electrode sheet is 25 mm), and the nickel tab is laser welded in the above positive electrode tab welding area; and then after passing through a roller, embossing is performed from the first surface to the second surface in the double-sided coating area (and avoiding the positive electrode tab welding area) to obtain a second concave portion (first surface) and a convex portion (second surface); the shape of the orthographic projection of the second concave portion and the convex portion on the surface of the positive electrode sheet is circular;

[0152] Among them, the mass content c of aluminum element in the positive electrode active coating is 11870ppm, the width of the second recess is 3mm, the depth is 30μm, and the spacing is 3mm; w1 is 9mm, w2 is 34mm, w3 is 20mm, w4 is 10mm, and w5 is 10mm.

[0153] (2) Preparation of negative electrode sheet

[0154] Artificial graphite (secondary particles), silicon-carbon material (the number of primary spherical particles accounts for 0.75 of the total number of primary spherical particles and secondary spherical particles, the average particle size of the primary spherical particles is 4.9 μm, and the mass content of element Si in the silicon-carbon material is 40%), negative electrode conductive agent (carbon nanotubes), negative electrode dispersant (lithium carboxymethyl cellulose) and negative electrode binder (polyacrylic acid) are mixed in a mass ratio of 77:20:0.4:0.1:2.5, and deionized water is added to prepare a negative electrode slurry; the above-mentioned negative electrode slurry is coated on the surface of both sides of the copper foil, and after baking and rolling, a negative electrode sheet with a thickness of 110 μm is obtained; a first concave portion (groove) is made on the surface of the negative electrode sheet using a laser;

[0155] The width of the groove is 99.7 μm, the depth is 29.9 μm, and the spacing is 1.5 mm.

[0156] (3) Preparation of electrolyte

[0157] In a glove box (H2O<0.01ppm, O2<0.01ppm, Ar atmosphere), ethylene carbonate, ethylene carbonate and diethyl carbonate are mixed in a weight ratio of 1:3:6 to obtain an organic solvent; fluoroethylene carbonate (FEC) and lithium hexafluorophosphate (LiPF6) are dissolved in the above-mentioned organic solvent to obtain an electrolyte; wherein the mass content of FEC in the electrolyte is 20%, and the mass content of LiPF6 in the electrolyte is 12.5%.

[0158] (4) Preparation of diaphragm

[0159] 1,3,5-triazine-2,4,6-triamine and polyacrylonitrile are ground, and then mixed with styrene-butadiene rubber and lithium polyacrylate in a mass ratio of 1:95:2:2 (1,3,5-triazine-2,4,6-triamine: polyacrylonitrile: styrene-butadiene rubber: lithium polyacrylate), and NMP is added to obtain an organic coating slurry; the organic coating slurry is applied to one surface of a polyethylene film (with a thickness of 5 μm), and dried (to form an organic coating with a thickness of 2 μm and an average particle size of polymer particles of 0.9 μm); A second adhesive layer of PMMA is coated on the other surface of the polyethylene film (forming a second adhesive layer with a thickness of 2 μm), and a first adhesive layer (including PVDF+PMMA, wherein the mass ratio of PVDF to PMMA is 7:3, forming a first adhesive layer with a thickness of 0.8 μm) is coated on the outer surface of the organic coating to obtain a diaphragm, wherein the mass content of nitrogen in the organic coating is 17%, the mass content of carbon in the organic coating is 68%, and the ratio of the mass content of carbon in the organic coating to the mass content of nitrogen is 4.

[0160] (5) Preparation of batteries

[0161] The positive electrode sheet prepared in step (1), the separator prepared in step (4) and the negative electrode sheet prepared in step (2) are wound to obtain a winding core (wherein the organic coating faces the positive electrode sheet); a battery is obtained by packaging, baking, liquid injection, formation, secondary sealing, sorting and OCV;

[0162] Among them, c×h is 0.0237.

[0163] Example 4 Group

[0164] This group of examples is used to verify the impact of changes in the "mass content of silicon in silicon-carbon materials".

[0165] This group of examples is carried out with reference to Example 1, except that the mass content of silicon in the silicon-carbon material is changed, as follows:

[0166] In Example 4a, the mass content of silicon in the silicon-carbon material is 51%;

[0167] In Example 4b, the mass content of silicon in the silicon-carbon material is 62%;

[0168] In Example 4c, the mass content of silicon in the silicon-carbon material is 30%;

[0169] In Example 4d, the mass content of silicon in the silicon-carbon material is 71%.

[0170] Example 5 Group

[0171] This group of examples is used to verify the impact of changes in the "average particle size of primary spherical particles".

[0172] This group of examples is carried out with reference to Example 1, except that the average particle size of the spherical particles is changed once, as follows:

[0173] Example 5a, the average particle size of the primary spherical particles is 1.2 μm;

[0174] In Example 5b, the average particle size of the primary spherical particles is 5.9 μm.

[0175] Example 6 Group

[0176] This group of examples is used to verify the influence of the change of "the mass content c of aluminum element in the positive electrode active coating".

[0177] This group of examples is carried out with reference to Example 1, except that c is changed as follows:

[0178] Example 6a, c is 6021 ppm; wherein c×h is 0.0096;

[0179] In Example 6b, c is 14955 ppm; wherein c×h is 0.0239.

[0180] Example 7 Group

[0181] This group of examples is used to verify the influence of the change of "the thickness h of the organic coating layer".

[0182] This group of examples is carried out with reference to Example 1, except that h is changed as follows:

[0183] Example 7a, h is 0.5 μm; wherein c×h is 0.0041;

[0184] In Example 7b, h is 4 μm; wherein c×h is 0.0327.

[0185] Example 8 Group

[0186] This group of examples is used to verify the influence of the change of "the product c×h of the mass content c of the aluminum element in the positive electrode active coating and the thickness h of the organic coating".

[0187] This group of examples is carried out with reference to Example 1, except that c×h is regulated by changing c and h, as follows:

[0188] Example 8a, c is 6122 ppm, h is 0.5 μm; wherein c×h is 0.0031;

[0189] In Example 8b, c1 is 14876 ppm, and h is 4 μm; wherein c×h is 0.0595.

[0190] Example 9 Group

[0191] This group of examples is used to verify the impact of changes in "the ratio of the mass content of carbon element to the mass content of nitrogen element in the organic coating".

[0192] This group of examples is carried out with reference to Example 1, except that the ratio of the mass content of carbon element to the mass content of nitrogen element in the organic coating is changed by changing the formula of the organic coating slurry, as follows:

[0193] In Example 9a, the mass ratio of 1,3,5-triazine-2,4,6-triamine, polyacrylonitrile, styrene-butadiene rubber and lithium polyacrylate is 70:25:3:2, wherein the mass content of nitrogen in the organic coating is 53%, the mass content of carbon in the organic coating is 43%, and the ratio of the mass content of carbon to the mass content of nitrogen in the organic coating is 0.81;

[0194] In Example 9b, the mass ratio of 1,3,5-triazine-2,4,6-triamine, polyacrylonitrile, styrene-butadiene rubber and lithium polyacrylate is 5:90:3:2, wherein the mass content of nitrogen in the organic coating is 12%, the mass content of carbon in the organic coating is 76%, and the ratio of the mass content of carbon in the organic coating to the mass content of nitrogen is 6.33.

[0195] Example 10 Group

[0196] This group of embodiments is used to verify the influence of the change of the “thickness of the first adhesive layer”.

[0197] This group of examples is carried out with reference to Example 1, except that the thickness of the first adhesive layer is changed, as follows:

[0198] In Example 10a, the thickness of the first adhesive layer is 1 μm;

[0199] In Example 10b, the thickness of the first adhesive layer is 0.2 μm;

[0200] In Example 10c, the thickness of the first adhesive layer is 3 μm.

[0201] Example 11 Group

[0202] This group of embodiments is used to verify the influence brought by the change of the "thickness of the second adhesive layer".

[0203] This group of examples is carried out with reference to Example 1, except that the thickness of the second adhesive layer is changed, as follows:

[0204] In Example 11a, the thickness of the second adhesive layer is 1.5 μm;

[0205] In Example 11b, the thickness of the second adhesive layer is 0.2 μm;

[0206] In Example 11c, the thickness of the second adhesive layer is 3 μm.

[0207] Example 12

[0208] This embodiment is used to verify the influence of changing the “type of the first recess”.

[0209] The process is carried out in accordance with Example 1, except that a laser is used to make recessed holes on the surface of the negative electrode sheet, wherein the width of the recessed holes is 93.4 μm, the depth is 25.5 μm, and the spacing is 0.5 mm.

[0210] Example 13 Group

[0211] This group of examples is used to verify the impact of changes in "the value of the number of primary spherical particles to the total number of primary spherical particles and secondary spherical particles".

[0212] This group of examples is carried out with reference to Example 1, except that the number ratio of spherical particles is changed once, as follows:

[0213] Example 13a, the number of primary spherical particles accounts for 0.1 of the total number of primary spherical particles and secondary spherical particles;

[0214] Example 13b, the number of primary spherical particles accounts for 0.89 of the total number of primary spherical particles and secondary spherical particles;

[0215] In Example 13c, all silicon-carbon materials are primary spherical particles, that is, the number of primary spherical particles accounts for 1 of the total number of primary spherical particles and secondary spherical particles.

[0216] Embodiment 14

[0217] The process is carried out in accordance with Example 1, except that the artificial graphite is primary particles with an average particle size of 6.1 μm.

[0218] Embodiment 15

[0219] This example is used to verify the influence of “whether the second concave portion is located on the surface of the positive electrode active coating on the first surface and whether the convex portion is located on the surface of the positive electrode active coating on the second surface”.

[0220] The method is carried out in accordance with Example 1, except that the embossing treatment is performed from the second surface to the first surface, that is, the surface of the positive electrode active coating on the second surface has a second concave portion, and the surface of the positive electrode active coating on the first surface has a convex portion.

[0221] Example 16

[0222] This example is used to verify the influence of “no second concave portion and convex portion being provided on the surface of the positive electrode active coating layer”.

[0223] The same process is carried out as in Example 1, except that no embossing treatment is performed.

[0224] Embodiment 17

[0225] This embodiment is used to verify the influence of "whether the single-sided coating area has a second concave portion".

[0226] The process is carried out in accordance with Example 1, except that embossing is performed on the single-sided coating area and the double-sided coating area (avoiding the positive electrode tab welding area).

[0227] Example 18 Group

[0228] This group of embodiments is used to verify the impact of changes in "w1, w2, w3, w4 and w5".

[0229] This group of examples is carried out with reference to Example 1, except that w1, w2, w3, w4 and w5 are changed as follows:

[0230] In Example 18a, w1 is 0.5 mm, w2 is 2 mm, w3 is 2 mm, w4 is 0.5 mm, and w5 is 0.5 mm;

[0231] In Example 18b, w1 is 10 mm, w2 is 40 mm, w3 is 25 mm, w4 is 20 mm, and w5 is 20 mm.

[0232] The above embodiments all meet the following requirements: the XRD diffraction pattern of the organic coating has a characteristic peak at 2θ of 19.5°-23.5°. The average particle size of the first lithium cobalt oxide particles is 0.3 μm-7 μm, and the average particle size of the second lithium cobalt oxide particles is 7.5 μm-40 μm.

[0233] Except for Example 16, the above embodiments all satisfy the following conditions: the height of the convex portion is 3 μm-40 μm, the width of the convex portion is 0.2 mm-8 mm, and the spacing between the convex portions is 0.2 mm-8 mm. Except for Example 13c, all the above embodiments all satisfy the following conditions: the average particle size of the secondary spherical particles is 3 μm-20 μm. Except for Example 14, all the above embodiments all satisfy the following conditions: the average particle size of the secondary particles is 6 μm-20 μm.

[0234] Test Case I

[0235] Adhesion test

[0236] The batteries prepared in the examples were tested for adhesion between the negative electrode sheet and the separator, and adhesion between the positive electrode sheet and the separator. The results showed that all examples met the following requirements: the adhesion between the negative electrode sheet and the separator was 10N / m-40N / m; the adhesion between the positive electrode sheet and the separator was ≤10N / m.

[0237] Comparative Example 1

[0238] The method was carried out with reference to Example 1, except that the average particle size of the spherical particles was changed as follows:

[0239] In Comparative Example 1a, the average particle size of the primary spherical particles was 0.7 μm;

[0240] In Comparative Example 1b, the average particle size of the primary spherical particles was 6.5 μm.

[0241] Comparative Example 2

[0242] The method is carried out in accordance with Example 1, except that the mass content c of the aluminum element in the positive electrode active coating is changed as follows:

[0243] Comparative Example 2a, c is 5643ppm;

[0244] Comparative Example 2b, c was 17965 ppm.

[0245] Comparative Example 3

[0246] The same method as in Example 1 was used, except that the organic coating was replaced with a boehmite ceramic coating of the same thickness.

[0247] Comparative Example 4

[0248] The process is carried out in accordance with Example 1, except that the organic coating faces the negative electrode sheet.

[0249] Comparative Example 5

[0250] The method is carried out with reference to Example 1, except that the thickness h of the organic coating is changed as follows:

[0251] Comparative Example 5a, h is 0.3 μm;

[0252] In comparative example 5b, h is 4.5 μm.

[0253] Comparative Example 6

[0254] The process is carried out in accordance with Example 1, except that no FEC is added to the electrolyte.

[0255] Test Case II

[0256] (1) Volume energy density test

[0257] The batteries prepared in the examples and comparative examples were tested for volume energy density, and the specific test method is as follows:

[0258] The battery was charged to 4.48V at a current of 0.2C, then charged at a constant voltage until the current dropped to 0.02C, and then discharged at a current of 0.2C to 3.0V, with the discharged energy recorded as E; the thickness, width and length of the battery were measured and the product of the three was calculated to obtain the volume of the battery recorded as V. The calculation formula for volume energy density is VED = E / V, and the results are recorded in Table 1.

[0259] (2) Fast charging performance test

[0260] The batteries prepared in the examples and comparative examples were tested for fast charging performance, and the specific test method is as follows:

[0261] Place it in a 25℃ constant temperature box for 2 hours, use 0.2C constant current to discharge to 3.0V, and let it rest for 5 minutes; then use 3C constant current to charge to 4.2V, switch to 2.5C constant current to charge to 4.25V, switch to 2C constant current to charge to 4.48V (1.2C end), record the time of 3C constant current charging to 4.2V (the longer the time, the better the fast charging performance), set the blue power to record the time every 1s, and record the results in Table 1.

[0262] (3) Cycle test

[0263] The batteries prepared in the examples and comparative examples were subjected to cycle tests, and the specific test methods are as follows:

[0264] Place it in a constant temperature room at 45℃ for 2h, charge it to 4.2V with 3C constant current, charge it to 4.25V with 2.5C constant current and constant voltage, charge it to 4.48V with 2C constant current and constant voltage, stop at 0.05C, place it for 10min; then discharge it to 3.0V with 0.7C, and cycle it for 500 times. The discharge capacity is C1, and the discharge capacity at the first full charge is C0. Then C1 / C0 is the capacity retention rate after 500 cycles. The results are recorded in Table 1.

[0265] (4) High temperature safety test

[0266] The batteries prepared in the examples and comparative examples were subjected to high temperature safety tests, and the specific test methods are as follows:

[0267] At room temperature (25°C), 0.5C constant current and constant voltage were set to 4.48V, and 0.05C was used to fully charge the battery. The fully charged battery was placed in a high temperature box, and the temperature was raised to 130°C at 5°C / min. The temperature was kept for 1 hour. 100 pcs of batteries were tested, and the pass rate was recorded in Table 1. The pass standard is: the battery does not catch fire or explode.

[0268] Table 1

[0269]

[0270]

[0271] It can be seen from Table 1 that, compared with the comparative example, the battery of the present invention can take into account high energy density, fast charging capability, excellent cycle stability and high temperature safety performance at a high charging cut-off voltage.

[0272] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A lithium ion secondary battery, characterized in that: It comprises a negative electrode sheet, a positive electrode sheet, a separator and an electrolyte; the charging cut-off voltage of the lithium-ion secondary battery is ≥4.48V; The negative electrode sheet comprises a silicon-carbon material, wherein the mass content of silicon in the silicon-carbon material is 30%-80%; The positive electrode sheet includes a positive electrode active coating, the positive electrode active coating includes lithium cobalt oxide, the lithium cobalt oxide contains aluminum element, and the mass content c of the aluminum element in the positive electrode active coating is 6000ppm-15000ppm; The separator includes an organic coating, the organic coating faces the positive electrode sheet; the organic coating includes polymer particles, the polymer particles contain nitrogen, and the thickness h of the organic coating is 0.5 μm-4 μm; The electrolyte comprises fluoroethylene carbonate, and the mass content of fluoroethylene carbonate in the electrolyte is 5%-30%; The mass content of nitrogen in the organic coating is 10.5%-55%.

2. The lithium ion secondary battery according to claim 1, wherein The silicon-carbon material comprises primary spherical particles, and the average particle size of the primary spherical particles is 1 μm-6 μm, preferably 3 μm-5 μm; And / or, the mass content c of aluminum element in the positive electrode active coating is 6500ppm-12000ppm; And / or, the negative electrode sheet further includes graphite material.

3. The lithium ion secondary battery according to claim 1 or 2, wherein: The mass content c of aluminum element in the positive electrode active coating and the thickness h of the organic coating satisfy: 0.003≤c×h≤0.06, where the unit of h is μm; Preferably, 0.0065≤c×h≤0.

024.

4. The lithium ion secondary battery according to claim 1 or 2, wherein: The polymer particles include at least one of cyano, isocyano, isocyanate and triazine groups; preferably, the polymer particles include at least one of polyacrylonitrile, nitrile rubber, 1,3,5-triazine-2,4,6-triamine, melamine cyanurate and melamine thiocyanate; And / or, the polymer particles further contain carbon, and the ratio of the mass content of carbon to the mass content of nitrogen in the organic coating is 0.7-7.6; preferably 1.5-4; And / or, the XRD diffraction pattern of the organic coating has a characteristic peak at 2θ of 19.5°-23.5°.

5. The lithium ion secondary battery according to claim 4, wherein: The mass content of carbon in the organic coating is 40%-80%, preferably 50%-70%; And / or, the mass content of nitrogen in the organic coating is 15%-35%.

6. The lithium ion secondary battery according to claim 1 or 2, wherein: The diaphragm further comprises at least one of a substrate layer, a first adhesive layer, and a second adhesive layer; Preferably, the thickness of the substrate layer is 3 μm-6 μm; Preferably, the thickness of the first adhesive layer is 0.2 μm-3 μm; Preferably, the thickness of the second adhesive layer is 0.2 μm-3 μm.

7. The lithium ion secondary battery according to claim 6, wherein: The diaphragm includes the substrate layer, the organic coating layer located on one side of the substrate layer, the first adhesive layer located on the outer surface of the organic coating layer, and the second adhesive layer located on the other side of the substrate layer; Preferably, the thickness of the first adhesive layer is 0.2 μm-1 μm; more preferably 0.3 μm-0.8 μm; Preferably, the thickness of the first adhesive layer is 1.5 μm-3 μm; more preferably 2 μm-2.5 μm.

8. The lithium ion secondary battery according to claim 1 or 2, wherein: The adhesion force between the negative electrode sheet and the separator is greater than the adhesion force between the positive electrode sheet and the separator; Preferably, the adhesion force between the negative electrode sheet and the separator is 10 N / m - 40 N / m; Preferably, the adhesion force between the positive electrode sheet and the separator is ≤ 10 N / m.

9. The lithium ion secondary battery according to claim 1 or 2, wherein: The negative electrode sheet includes a negative current collector and a negative active coating located on at least one surface of the negative current collector; the outer surface of the negative active coating has a first recess; Preferably, the depth of the first recess is 5 μm - 40 μm; Preferably, the width of the first recess is 40 μm - 200 μm; Preferably, the spacing of the first recesses is 0.5 mm - 5 mm.

10. The lithium ion secondary battery according to claim 1 or 2, wherein: The positive electrode sheet includes a positive current collector and the positive active coating located on at least one surface of the positive current collector; the length of the positive active coating located on the first surface of the positive current collector is greater than the length of the positive active coating located on the second surface of the positive current collector; The region where the projection of the positive active coating located on the first surface overlaps with the projection of the positive active coating located on the second surface in the thickness direction of the positive electrode sheet is the double-sided coating region, and the region where the projections do not overlap is the single-sided coating region; The surface of the positive active coating located on the first surface has a second recess, and the surface of the positive active coating located on the second surface has a protrusion; Preferably, the positive electrode sheet includes a pasting area, the pasting area includes the double-sided coating area and the single-sided coating area, and the second recess and the protrusion are located in the double-sided coating area; Preferably, the positive electrode sheet includes a positive tab welding area, a pasting area and a bare foil area, and the second recess and the protrusion are located in the pasting area; Preferably, the depth of the second recess is 3 μm - 40 μm, the width of the second recess is 0.2 mm - 8 mm, and the spacing of the second recesses is 0.5 mm - 8 mm; Preferably, the height of the protrusion is 3 μm - 40 μm, the width of the protrusion is 0.2 mm - 8 mm, and the spacing of the protrusions is 0.5 mm - 8 mm.

11. The lithium ion secondary battery according to claim 10, wherein: The positive electrode sheet includes a positive tab welding area, a pasting area and a bare foil area, and the pasting area includes the double-sided coating area and the single-sided coating area; The distance from the second recess to the edge of the positive tab welding area is w1, 0 mm < w1 ≤ 10 mm; And / or, the distance from the second recess to the edge of the first side of the pasting area is w2, 2 mm ≤ w2 ≤ 40 mm, and the first side is the side where the positive tab welding area is provided; And / or, the distance from the second recess to the edge of the second side of the pasting area is w3, 2 mm ≤ w3 ≤ 25 mm, and the second side is the side opposite to the side where the positive tab welding area is provided; And / or, the distance from the second recess to the edge of the third side of the pasting area is w4, 0 mm < w4 ≤ 20 mm, and the third side is the side of the pasting area close to the starting end of winding; And / or, the distance from the second recess to the boundary line between the double-sided coating area and the single-sided coating area is w5, 0 mm < w5 ≤ 20 mm.

Citation Information

Patent Citations

  • High energy density polymer lithium ion battery and preparation method thereof

    CN110391414A

  • Electrolyte and battery

    CN118099518A

  • Lithium ion battery and electric equipment

    CN118943468A

  • Secondary battery and electronic device

    WO2024197943A1

Cited By

  • Lithium-ion secondary battery

    WO2026145585A1